2008
DOI: 10.1038/ncb1753
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of TORC1 by Rag GTPases in nutrient response

Abstract: TORC1 (Target of rapamycin complex 1) has a critical role in the regulation of cell growth and cell size. A wide range of signals, including amino acids, is known to activate TORC1. Here, we report the identification of Rag GTPases as novel activators of TORC1 in response to amino acid signals. Knockdown of Rag gene expression suppressed the stimulatory effect of amino acids on TORC1 in Drosophila S2 cells. Expression of constitutively active (GTP-bound) Rag in mammalian cells enhances TORC1 in the absence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
1,165
2
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,186 publications
(1,204 citation statements)
references
References 48 publications
32
1,165
2
5
Order By: Relevance
“…Accordingly, expression of a constitutively active (GTP-bound) Gtr1 GTP , which interacted strongly with TORC1, rendered TORC1 partially resistant to leucine deprivation, while expression of a growth inhibitory GDP-bound Gtr1 GDP caused constitutively low TORC1 activity. In line with this proposed model in yeast, two complementary studies in Drosophila and mammalian cells have also reported that the conserved Rag GTPases act as upstream regulators of TORC1 and play important roles in coupling amino acid-derived signals to TORC1 (Kim et al 2008;Sancak et al 2008).…”
Section: How Is Tor Signalling Regulated?mentioning
confidence: 61%
“…Accordingly, expression of a constitutively active (GTP-bound) Gtr1 GTP , which interacted strongly with TORC1, rendered TORC1 partially resistant to leucine deprivation, while expression of a growth inhibitory GDP-bound Gtr1 GDP caused constitutively low TORC1 activity. In line with this proposed model in yeast, two complementary studies in Drosophila and mammalian cells have also reported that the conserved Rag GTPases act as upstream regulators of TORC1 and play important roles in coupling amino acid-derived signals to TORC1 (Kim et al 2008;Sancak et al 2008).…”
Section: How Is Tor Signalling Regulated?mentioning
confidence: 61%
“…Amino acid levels are linked to mTOR through a mechanism that is dependent, at least to some extent, on p62/ SQSTM1 (Duran et al 2011): mTORC1 associates with the amino acid sensing Rag family of small GTPases (Kim et al 2008;Sancak et al 2008) on the surface of lysosomes (Sancak et al 2010). p62/SQSTM1 mediates this process by associating with Raptor, a subunit of the mTORC1 complex, and the Rag GTPases, thereby forming a high molecular weight complex that relays the signal from amino acids to the mTORC1 pathway (Duran et al 2011).…”
Section: Amino Acid Sensing: Mtormentioning
confidence: 99%
“…In mammalian cells, the activity of Rag GTPase complexes depends on whether RagA and RagB are bound to GTP or GDP. The Rag GTPase complex containing GTP-bound RagA or RagB activates mTORC1 signaling, whereas the complex containing GDP-bound RagA or RagB does not activate mTORC1 (Kim et al, 2008;Sancak et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Amino acids, especially the branched chain amino acids such as leucine, are potent inducers of mTORC1 activation. The amino acid-regulated mTORC1 pathway is mediated by Rag GTPase heterodimers and their associated proteins on the lysosome (Kim and Guan, 2009;Kim et al, 2008;Sancak et al, 2008;. Rag GTPases are evolutionarily conserved throughout eukaryotes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation